Calcários albianos de campo petrolífero na Bacia de Campos: fácies, diagênese e modelo deposicional - Okubo, Juliana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Carbonate rocks from the Macaé Group (Albian), particularly the Quissamã Formation, are important reservoirs of the Campos Basin. A fundamental problem related to modelling of hydrocarbon reservoirs is the characterization of petrophysical heterogeneties, which is closely related to temporal and spatial variability of sedimentological properties (i.e., depositional model). Geological models previously presented for Macaé Group rocks show facies and their lateral variation. On the other hand, those models lack information about depositional processes of these facies. This work presents depositional model for Macaé Group carbonates including the upper part of the Quissamã Formation and the lower part of the Outeiro Formation. The studied interval comprises a 200-400m thick section within an oil field located in southwest portion of the Campos Basin. Facies and facies associations (FA) were defined by macroscopic analyses of rocks (320m cores), supported by microscopic analyses. Electrofacies were created by supervised and unsupervised approaches in 28 wells. Distinct sedimentary cycles with three diferent scales (high, medium, low) were interpreted based on the vertical facies sucession. Eleven sedimentary facies were recognized: A) oolitic grainstone, (B) oncolitic grainstone, (C) oncolitic peloidal grainstone, (D) oncolitic bioclastic packstone, (E) peloidal bioclastic packstone, (F) bioclastic packstone, (G) oolitic packstone/wackestone, (H) wackestone, (I) pithonellids wackestone, (J) bioclastic wackestone with glauconite e (K) dolomite. Facies A to H represent rocks of the Quissamã Formation whereas facies I and J represent rocks of the Outeiro Formation. Facies association A+B (FA1) is related to deposition in shallow depths, above the fair weather wave base (FWWB). Facies C and D (FA2) were formed in waters slightly weaker or more sporadic than FA1, close to the FWWB. Facies association E+H (FA3) is related to calm waters...

Alguns dos depósitos carbonáticos do Grupo Macaé (Albiano), sobretudo na Formação Quissamã, correspondem a importantes reservatórios na Bacia de Campos. O problema fundamental na modelagem de reservatórios de hidrocarbonetos é a caracterização das heterogeneidades petrofísicas, as quais estão intimamente relacionadas à variabilidade temporal e espacial das propriedades sedimentológicas (modelo deposicional). Modelos anteriormente propostos para estas rochas mostram as fácies presentes e a variação lateral entre elas. No entanto, não detalham os processos deposicionais formadores destas fácies. Este trabalho tem como objetivo construir um modelo deposicional para os carbonatos do Grupo Macaé - englobando o intervalo superior da Fm. Quissamã e porção basal da Fm. Outeiro, em um total de cerca de 200 a 400 metros de espessura - em um campo petrolífero (área de 32km2) a sudoeste da Bacia de Campos. Os tipos de fácies e as associações de fácies (AF) foram definidos a partir da análise macroscópica de 320 metros de testemunhos, com auxílio da análise microscópica. A análise das 237 lâminas delgadas também possibilitou reconhecer a história diagenética das rochas estudadas. Foram geradas fácies a partir de perfis geofísicos (eletrofácies) pelo método de redes neurais segundo as aprendizagens supervisionada e não-supervisionada em 28 poços - de testemunhagem mais contínua, menos contínua e sem testemunhos. A partir do empilhamento das fácies definido nos testemunhos, foram interpretados ciclos em três diferentes hierarquias: alta, média e baixa frequência. Reconheceram-se onze fácies sedimentares: (A) grainstone oolítico, (B) grainstone oncolítico, (C) grainstone oncolítico peloidal, (D) packstone oncolítico bioclástico, (E) packstone peloidal bioclástico, (F) packstone bioclástico, (G) packstone/wackestone oolítico, (H) wackestone, (I) wackestone a pitonelídeos, (J) wackestone...
Keywords: Geology; Geologia; Petrologia; Geologia estratigráfica; Carbonatos; Rochas carbonaticas; Calcario; Sedimentação e depósitos; Reservatórios de hidrocarbonetos; Facies (Geologia); Campos, Bacia de (RJ)